2022
DOI: 10.1128/spectrum.01204-22
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Evolution of Unique Plasmids Harboring bla IMP-70 and bla CTX-M-253 in Multidrug-Resistant Providencia rettgeri

Abstract: Although Providencia rettgeri is an opportunistic pathogen, its intrinsic resistance to colistin and tigecycline makes the treatment of carbapenem-resistant P. rettgeri challenging. We isolated a multidrug-resistant P. rettgeri strain which harbored a rare bla IMP variant, bla IMP-70 , a novel bla CTX-M variant, bla … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…bla IMP-70 and bla CTX-M-253 in multidrug-resistant Providencia Rettgeri and suggested that the cointegration of plasmids in P . rettgeri may not be unusual and may play a role in the transmission of clinically relevant b-lactamases ( Watanabe et al, 2022 ). In our study, one class 1 integron was identified in p18004577_NDM, which harbored multiple resistance genes, such as bla O XA -10 , ant ( 2′ ) -Ia , catB8 , bla PER-4 , and two Δsul1 .…”
Section: Discussionmentioning
confidence: 99%
“…bla IMP-70 and bla CTX-M-253 in multidrug-resistant Providencia Rettgeri and suggested that the cointegration of plasmids in P . rettgeri may not be unusual and may play a role in the transmission of clinically relevant b-lactamases ( Watanabe et al, 2022 ). In our study, one class 1 integron was identified in p18004577_NDM, which harbored multiple resistance genes, such as bla O XA -10 , ant ( 2′ ) -Ia , catB8 , bla PER-4 , and two Δsul1 .…”
Section: Discussionmentioning
confidence: 99%